Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/bios12110987
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Attomolar SARS-CoV-2 Nucleic Acids in All-Dielectric Metasurface Biosensors

Abstract: Worldwide infection due to SARS-CoV-2 revealed that short-time and extremely high-sensitivity detection of nucleic acids is a crucial technique for human beings. Polymerase chain reactions have been mainly used for the SARS-CoV-2 detection over the years. However, an advancement in quantification of the detection and shortening runtime is important for present and future use. Here, we report a rapid detection scheme that is a combination of nucleic acid amplification and a highly efficient fluorescence biosens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The MF chip was made of polydimethylsiloxane (PDMS), which was transparent to visible light and was designed to have six MF paths in accordance with the six metasurface areas ( Figure 1 c). Inlet and outlet holes were introduced at both ends of each MF path to facilitate connecting from the outside; this can be seen in previous reports [ 20 , 21 ]. The PDMS was naturally absorbed on the metasurface substrate, enabling us to flow the liquid reagents.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MF chip was made of polydimethylsiloxane (PDMS), which was transparent to visible light and was designed to have six MF paths in accordance with the six metasurface areas ( Figure 1 c). Inlet and outlet holes were introduced at both ends of each MF path to facilitate connecting from the outside; this can be seen in previous reports [ 20 , 21 ]. The PDMS was naturally absorbed on the metasurface substrate, enabling us to flow the liquid reagents.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, biosensors applicable to cancer markers were often tested for their robustness using human serums [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. All-dielectric metasurface biosensors [ 18 , 19 , 20 , 21 ] and plasmon–photon hybrid metasurface biosensors [ 22 ] were recently reported as efficient fluorescence (FL) biosensors. Figure 1 a,b illustrates two situations where sandwich complexes of antibody (Ab)—antigen—Ab are formed.…”
Section: Introductionmentioning
confidence: 99%
“…Iwanaga et al [ 118 ] reported that a meta surface biosensor made up of an all-dielectric meta surface and a microfluidic transparent chip is described as a fast identification method that chains DNA magnification and a precise fluorescence biosensor. The meta surface biosensors recognized amplicons coming from attomolar SARS-CoV-2 nucleic acids, and the magnification was carried out within an hour, according to a series of proof-of-principle experimental results executed in the present scheme ( Figure 5 C).…”
Section: Nucleic Acid-based Biosensorsmentioning
confidence: 99%
“… ( A ) Overview of the process and microscopic cross section of channel and electrodes [ 116 ] ( B ) Schematic of the LoC developed by STMicroelectronics [ 117 ] ( C ) Schematic of meta surface biosensors [ 118 ] ( D ) Schematic of dielectric meta surface structure and the whole view of meta surface substrate [ 119 ]. …”
Section: Figurementioning
confidence: 99%
“…Optical biosensors are widely used for biomedical research, healthcare, and environmental monitoring. Compared with standard optical sensors based on fluorescence measurement, label-free nanophotonic sensors do not need to label biomolecules, which reduces the effort involved in sample preparation and enables rapid analysis in real time [ 13 , 14 , 15 , 16 , 17 ]. The performance of a sensor can be characterized by the detection limit, which is inversely proportional to the product of the quality factor ( ) of the resonance and the refractive index sensitivity ( ) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%